2014
DOI: 10.1155/2014/769790
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the All-Oral Schedule of Metronomic Vinorelbine and Capecitabine in Locally Advanced or Metastatic Breast Cancer Patients: The Phase I-II VICTOR-1 Study

Abstract: Background. Vinorelbine (VRB) and capecitabine (CAPE) are demonstrated to be active in pretreated metastatic breast cancer patients. Different studies have demonstrated that the metronomic treatment is active with an acceptable toxicity profile. We designed a Phases I-II study to define the MTD of oral metronomic, VRB, and CAPE. Patients and Methods. Phase I: fixed dose of CAPE was 500 mg thrice a day, continuously. Level I of VRB was 20 mg/tot thrice a week for 3 weeks (1 cycle). Subsequent levels were 30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 13 publications
2
38
0
2
Order By: Relevance
“…In another study [6], the combination of a low protracted dose of temozolomide, mVNR, and radiotherapy for newly diagnosed brain metastases from breast cancer resulted in CBR of 77 % and ORR of 52 %. Finally, the single-center phase I/II VICTOR-1 study [4] reported similar results to those shown by other studies with a clinical benefit rate (CBR) of 58.1 %. Taken together, these data and those from the present study suggest that mCT, when administered with highly active and synergistic drugs such as VNR and CAPE, is able to induce encouraging DCR.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In another study [6], the combination of a low protracted dose of temozolomide, mVNR, and radiotherapy for newly diagnosed brain metastases from breast cancer resulted in CBR of 77 % and ORR of 52 %. Finally, the single-center phase I/II VICTOR-1 study [4] reported similar results to those shown by other studies with a clinical benefit rate (CBR) of 58.1 %. Taken together, these data and those from the present study suggest that mCT, when administered with highly active and synergistic drugs such as VNR and CAPE, is able to induce encouraging DCR.…”
Section: Discussionsupporting
confidence: 77%
“…Several phase II studies have investigated metronomic vinorelbine (mVNR) in the treatment of breast cancer [48]. mVNR demonstrated long-lasting disease control combined with a good toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 31 patients evaluable for efficacy 58,1% obtained a clinical benefit. With regard to the safety, two cases of grade 4 leukopenia one case of grade 3 thrombocytopenia, and one case of grade II diarrhea were observed [68]. Vinorelbine was also evaluated together with cyclophosphamide in a small phase II study conducted by Pluma Jimenez et al In this study 20 patients previously treated with anthracyclines and taxanes were evaluated.…”
Section: Breast Cancermentioning
confidence: 99%
“…This trial showed that this metronomic combination was a well-tolerated and feasible regimen with 2 complete and 10 partial responses documented [37]. In the phase I/II VICTOR-1 study, the combination of metronomic vinorelbine thrice weekly and capecitabine 500 mg thrice daily was investigated [38]. The dosage of vinorelbine could be increased up to 40 mg thrice weekly.…”
Section: Metronomic Schedulesmentioning
confidence: 99%